#TITLE_ALTERNATIVE# - PRIMA ARIEF (NIM 10104001), EDHO
Super edge-magic labeling was introduced by Enomoto et al. in 1998. As a special case of edge-magic labeling, super edge-magic labeling is defined as a labeling of a graph of p vertices and q edges which maps all vertices to {1; 2; : : : ; p} and all edges to {p + 1; p + 2; : : : ; p + q} such that for any edges, the sum of its label and the labels of the vertices it connects, is the same. Some types of graph then proved to be not having super edge-magic labeling. This motivated Figueroa-Centeno et al. in 2002 to extend the concept of edge-magic deficiency which is used for edge-magic labeling to be used for super edge-magic labeling. Such concept, called super edge-magic deficiency, illustrates how close a graph to a graph which has super edge-magic labeling is. In this book, we studied the problem of finding deficiency value of some types of graph. Types of graph we studied are wheel, fan and double fan which were studied before by Ngurah et al. in 2007. This book extends their results with some new results.